1990
DOI: 10.1080/09593339009384902
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach to ozone ‐ water mass transfer using hollow ‐ fiber reactors

Abstract: A novel reactor system based on microporous hollow-fiber membranes is proposed for ozonewater systems. Results from experimentation, where ozone transfer is achieved via the hollow fibers into a closed circuit flow-through reactor configuration, indicate such systems may be superior to existing ozone transfer approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…where C m1 is the concentration at the gas-membrane interface on the membrane side and S is the solubility constant of the gas in the membrane. Previous studies, e.g., [13,18] on O 3 mass transfer often assumed the concentration of O3 at the gas-membrane is continuous i.e., C g,i = C m1 . In this work, comparison of the concentration profile at the gas-membrane interface for both cases is presented.…”
Section: Membranementioning
confidence: 99%
See 1 more Smart Citation
“…where C m1 is the concentration at the gas-membrane interface on the membrane side and S is the solubility constant of the gas in the membrane. Previous studies, e.g., [13,18] on O 3 mass transfer often assumed the concentration of O3 at the gas-membrane is continuous i.e., C g,i = C m1 . In this work, comparison of the concentration profile at the gas-membrane interface for both cases is presented.…”
Section: Membranementioning
confidence: 99%
“…The potential for large-scale operation of O 3 is limited by membrane durability under extreme oxidizing conditions [17]. Therefore, the choice of the membrane material in O 3 applications is critical [18,19]. Chemical-resistant membranes that have been used for ozonation of water consist of ceramic materials [20][21][22][23][24] and fluorinated [13,[25][26][27][28][29] or non-porous silicone based [26,30] polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States there is an increasing interest in the application of both ozone and membrane filtration for DBP and DBP precursor removal in order to meet the requirements of the Surface Water Treatment Rule (SWTR), the Disinfectant and Disinfectant Byproducts Rule (D/DBPR), and the Long Term 1 Enhanced Surface Water Treatment rule (LT1ESWTR). Several researchers have attempted to combine ozone with polymeric membranes with limited success, in part because the organic membranes, which are commonly used in water and wastewater treatment applications, are prone to destruction by ozone (6)(7)(8)(9). Hashino et al (9) studied the use of ozonation combined with an ozone resistant polyvinylidenefluoride (PVDF) microfiltration membrane.…”
Section: Introductionmentioning
confidence: 99%
“…7 Researchers using microporous polypropylene hollow-fiber membranes for gaseous ozone transfer to water found that ozone reacted with the fibers, decreasing the mass transfer rate of ozone and leaving the fibers brittle. 8 Membrane air-stripping was applied at pilot scale for assessment of its performance in treating a groundwater contaminated with trichloroethene (TCE). The process was used continuously for 75 days, and a 30 percent reduction in removal efficiency occurred over that period.…”
Section: Introductionmentioning
confidence: 99%